An Introduction to the Flint Hills and the Tallgrass Prairie - Rex Buchanan; Brian Obermeyer (Symphony in the Flint Hills, 2011)
It was Zebulon Montgomery Pike who first coined the name Flint Hills when exploring the region in 1806. In his journal, September 12th, he described the following near the headwaters of the Verdigris River in southeastern Chase County: “Commenced our march at seven o’clock. Passed very ruff flint hills. My feet blistered and very sore.” He went on to say that from one view he could see buffalo, elk, deer, cabrie [pronghorn], and panthers.
Keywords: Emerald Hills; soil; geology; limestone; chert; shale; ranching; ocean; sea; ancient Kansas; Cottonwood limestone; caves; native grass